Protein kinases in plant responses to drought, salt, and cold stress - Chen X.; Ding Y.; Yang Y.; Song C.; Wang B.; Yang S.; Guo Y.; Gong Z.
Protein kinases are major players in various signal transduction pathways. Understanding the molecular mechanisms behind plant responses to biotic and abiotic stresses has become critical for developing and breeding climate-resilient crops. In this review, we summarize recent progress on understanding plant drought, salt, and cold stress responses, with a focus on signal perception and transduction by different protein kinases, especially sucrose nonfermenting1 (SNF1)-related protein kinases (SnRKs), mitogen-activated protein kinase (MAPK) cascades, calcium-dependent protein kinases (CDPKs/CPKs), and receptor-like kinases (RLKs). We also discuss future challenges in these research fields. © 2021 Institute of Botany, Chinese Academy of Sciences
Keywords: CDPKS; COLD STRESS; DROUGHT STRESS; MAPK CASCADE; RLKS; SALT STRESS; SNRKS